Seeking markets and resources: state-driven Chinese and Indian investments in Zambia. (1st January 2012) - Kragelund, Peter; Hampwaye, Godfrey
Processes of globalisation are currently changing the global activity of multinational companies (MNCs). 'Emerging' MNCs are competing with 'conventional' MNCs when investing in new markets. This article sets out to analyse the motives and strategies of Chinese and Indian MNCs investing in Zambia. It argues that despite the different home-country contexts of these investments, emerging MNCs depict differences as well as similarities. Moreover, the article maintains that existing theories explaining international production provide a suitable framework to understand 'emerging' patterns, but that more emphasis must be placed on the home and host contexts and how institutional features impact investment decisions.